RESEARCH OF MAGNETIC-TRIBOLOGICAL INFLUENCE ON THE SURFACE ROUGHNESS PARAMETERS - Свирид, Михайло Миколайович; Сидоренко, Олександр Юрійович; Смірнов, Ігор Володимирович; Хижняк, Сергій Васильович (Problems of Friction and Wear, 2024)
The mechanism of topography change of tribological contact at a surface under the influence of a magnetic field (MP) of 0,3 T without greasing is opened in article. In the pair of friction SHH-15 on the counter-body of the diamagnetic class (glass). The roughness of the created tribological films under the conditions of the directed action of MP in the experimental surface is carried out. Using the criterion of optimization of roughness parameters (Ra, Rz) and the reference curve of the profile on the friction surface, a correlation was established between the wear resistance characteristics and the position of the Abbot-Firestone curve. The method of calculating the location of the middle line of the profile using the standard program AutoCAD is presented. It was found that the formation of surface films change the shape of the support surface and the direction of the Abbot-Firestone curve.